THE QUALITY OF COOKIES WITH THE SUBSTITUTION OF TEMPEH PEANUT FLOUR AND CILEMBU CULTIVAR SWEET POTATO FLOUR - Oktaviani, Yustina Wanda Dwi; Swasti, Yuliana Reni; Pranata, Franciscus Sinung (Fakultas Teknologi Pertanian Universitas Brawijaya, 2025)
A cookie is a biscuit made from wheat flour as its main ingredient. Cookies have a crunchy and less dense texture. Wheat flour can be substituted with peanut tempeh flour and Cilembu cultivar sweet potato flour to increase the nutritional value. This study aims to determine the effect of substituting peanut tempeh flour and Cilembu cultivar sweet potato flour on the nutritional quality of the cookie. Four treatments were employed in this study. The ratio of wheat flour, peanut tempeh flour, and Cilembu cultivar sweet potato flour is the basis of the treatment. The treatments are K (100:0:0), A (60:35:5), B (60:25:15), and C (60:15:25). The results of this study prove that the substitution increases the nutritional quality. The cookie with treatment A has the best nutritional quality. It has water content 3.61% - 4.22%, ash content 0.93% - 1.43%, protein content of 8.15% - 14.11%, fat content of 21.17% - 32.70 %, carbohydrate content 48.33 % - 66.13 %, insoluble fiber content 1.23 %-2.73 %, soluble fiber content 4.90-8.44 %, white-orange color, texture 20.76-43.89 N, total plate count 1 x 101 CFU/g - 3 x 102 CFU/g, and the negative content of yeasts and molds. The cookies with treatment A meet the requirements of Indonesian National Standard (INS) 2973:2018 and INS 01-2973-2011. Cookies with treatment A is the best product based on chemical, physical, microbiological, and organoleptic values.